2006
DOI: 10.1128/jb.00447-06
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxanthine Incorporation Is Nonmutagenic in Escherichia coli

Abstract: Endonuclease V, encoded by the nfi gene, initiates removal of the base analogs hypoxanthine and xanthine from DNA, acting to prevent mutagenesis from purine base deamination within the DNA. On the other hand, the RdgB nucleotide hydrolase in Escherichia coli is proposed to prevent hypoxanthine and xanthine incorporation into DNA by intercepting the noncanonical DNA precursors dITP and dXTP. Because many base analogs are mutagenic when incorporated into DNA, it is intuitive to think of RdgB as acting to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…At this point we measured the rate of AT3CG transversions in our wild-type and mutT mutant strains to compare them with the reported data. We found that, whereas the increase in mutagenesis due to the mutT defect matches the values reported in the previous studies, the absolute level of AT3CG transversions is up to two orders of magnitude lower because of the much lower basal level in our wild-type strain (which is confirmed in an independent study [12]). We have noticed an adaptive-like mutagenesis (26) in the CC101 strain, about a twofold increase in the number of Lac ϩ colonies between day 2 and day 8 ( Fig.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…At this point we measured the rate of AT3CG transversions in our wild-type and mutT mutant strains to compare them with the reported data. We found that, whereas the increase in mutagenesis due to the mutT defect matches the values reported in the previous studies, the absolute level of AT3CG transversions is up to two orders of magnitude lower because of the much lower basal level in our wild-type strain (which is confirmed in an independent study [12]). We have noticed an adaptive-like mutagenesis (26) in the CC101 strain, about a twofold increase in the number of Lac ϩ colonies between day 2 and day 8 ( Fig.…”
Section: Discussionsupporting
confidence: 76%
“…The main reason is that while the mutagenicity of our mutT allele is the same as the normalized mutation rates used in the previous studies (Table 3), the mutation rate in the CC101 strain is 22 to 125 times lower. It should be noted that a similarly low level of mutagenesis was already reported for this CC101 strain in an independent study from this laboratory (12). The calculated level of three to four 8-oxo-G modifications in the DNA of mutT mutants is 10 times lower than the steadystate level of endonuclease V-recognized modifications in the DNA of rdgB mutants (about 42 per genome equivalent) (10) and is even lower than the steady-state level of uracil excision events in dut mutants (16 per genome equivalent) (43) ( Table 4).…”
Section: Vol 189 2007mentioning
confidence: 88%
See 1 more Smart Citation
“…With respect to mutagenesis, while there is some controversy about the ability of hypoxanthine to induce mutations in E. coli (4,44), dI, dX, and dU are all established mutagens in higher organisms. So it is reasonable to assume that genetic polymorphisms that raise the steady-state levels of dX and dI in DNA in humans would exacerbate the toxicity associated with the nitrosative stress of chronic inflammation, with further increases in dX and dI exceeding the cell's repair capacity and contributing to mutations and cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Ham1p is a specific pyrophosphatase that hydrolyzes HAP deoxyribonucleoside triphosphate to the corresponding mononucleotide, thus preventing incorporation of the analog into DNA [4,8]. While E. coli contains a homolog for the HAM1 gene, named rdgB [9,10], this system apparently plays a back-up role in HAP detoxification [11,12]. Its main function is likely the removal of (d)ITP or (d)XTP from the cellular (d)NTP pools [10][11][12].…”
Section: Introductionmentioning
confidence: 99%